Skin breakdown in acute care pediatrics...this article originally appeared in Pediatric Nursing, 31(12), 132-138, 148, and is reprinted here with the permission of the publisher - Suddaby EC; Barnett SD; Facteau L (Dermatology Nursing, 2006)
The purpose of this study was to develop a simple, single page measurement tool that evaluates risk of skin breakdown in the pediatric population and apply it to the acutely hospitalized child.Data were collected over a 15-month period from 347 patients on four in-patient units (PICU, medical-surgical, oncology, and adolescents) on skin breakdown using the AHCPR staging guidelines and compared to the total score on the Starkid SkinScale in order to determine its ability to predict skin breakdown.The inter-rater reliability of the Starkid Skin Scale was r[2] = 0.85 with an internal reliablity of 0.71. The sensitivity of the total score was low (175%) but highly specific (98.5%). The prevalence of skin breakdown in the acutely hospitalized child was 23%, the majority (775%) occurring as erythema of the skin. Buttocks, perineum, and occiput were the most common locations of breakdown. Occiput breakdown was more common in critically ill (PICU) patients while diaper dermatitis was more common in the general medical-surgical population.